Effect of a mobile application on the precision of the preliminary diagnosis of anxiety. Issue 1 (1st January 2020) - Espinoza, Walter Junior Mayo; Paredes, Emigdio Antonio Alfaro
Abstract: There were not found studies about the impact of the use of a mobile application on the diagnostic precision of anxiety, which makes it difficult to make decisions to apply this technology to improve the sensitivity and specificity of this diagnosis, which is necessary due to millions of people around the world are affected by anxiety. The purpose of the research was to determine if a mobile application improved the process of preliminary diagnosis of the anxiety disorder of patients of the psychology service in a hospital with a convenience sample of 23 patients. The results of the study showed an improvement in sensitivity (from 33.3% to 83.3%) and a decrease in specificity (from 94.1% to 82.3%) of the preliminary diagnosis of this disorder. It was concluded that the use of the mobile application together with the color psychology allowed the increase of the sensitivity of the preliminary diagnosis and that the decrease of the specificity was a consequence of the better identification of patients with the diagnosis with this technological solution. For future researches, the recommendations included the use of the developed mobile application or other similar applications in other cities and countries, improving their functional and technical characteristics, as well as to study the results of the use of similar mobile applications for other psychological disorders.